Innovating instruction through team teaching - Sagge, Lina Flor Baña 1945- (College of Education, University of the Philippines Diliman, 1968)
The purpose of the study was to present pertinent facts and information about team teaching as to provide an insight into a more effective way of meeting individual differences in their respective schools. Contents of the study were largely obtained from various library resources. Team teaching as a complex structure entails major demands. Its success is determined by the setting in which it is attempted and the characteristics which function within the human dimension. Team members must essentially be compatible so that there will be no personality clashes and disagreements which will rupture the team process. This requires insight, perception, and virtuosity with human behavior on the part of the school administrators.